Measuring practice gaps in the delivery of evidence-based seating assessments: a retrospective chart review. (3rd April 2021) - Lo, Lorna; Hebert, Debbie; Colquhoun, Heather
Abstract: Purpose: To measure if a knowledge-to-practice gap exists between desired practice and current practice in wheelchair assessment after the implementation of a new seating assessment tool at a university affiliated rehabilitation centre. Methods: A 6-month retrospective chart review of 61 wheelchair assessments was undertaken to determine if the assessment was consistent with a newly implemented and evidence-based seating assessment tool. Descriptive statistics were used to analyse the data to determine the degree of completion of the 69-item assessment and across 61 individual assessments. Results: Of the 61 assessments reviewed, 69% were documented using the new seating assessment tool, 21% were documented using the previous seating assessment tool, and 10% were not documented on any seating assessment tool. Completion of the 69-item assessment tool was greater than 80% in 39% of the 61 assessments. The highest rates of completion were in the categories of patient information, clinical reasoning, and goals with an average completion of 73%, 71% and 65% respectively. The categories of linear measurements, mat assessment in supine, and postural alignment in wheelchair had the lowest average completion of 45%, 40% and 30% respectively. Conclusion: This chart review successfully identified and quantified areas of wheelchair assessment documented in adherence to current evidence-based guidelines, as well as gaps in assessment practice that should be addressed. Implication for rehabilitation: Completion of chart review is a simple tool to describe current practice and evaluate adherence to practice standards. Identifying practice gaps is an important first step in determining areas of focus in the improvement of clinical care. Ongoing support and monitoring is required in the development and implementation of evidence-based wheelchair assessment to ensure adoption in clinical practice.